Recognizing the Importance of an Urban Soil in an Open-Air City Museum: An Opportunity in the City of Madrid, Spain - Raimundo Jiménez-Ballesta; Isabel S. De Soto-García; Francisco Jesús García-Navarro; Rosario García-Giménez (Land, 2022)
This article examines the presence of urban soil buried under anthropogenic debris in an air-museum park in the Madrid city center (Spain), and highlights the particularities of this singular urbanized setting to indicate ecological evaluation options for soils. The study of a soil profile (with a thickness of about 2.30 m), classified as Urbic Technosols, allowed us to devise that it is formed by a series of filled-in amounts of artifacts (construction debris and other anthropogenic waste) of about 10–30%, plus organic and mineral materials. These soils’ composition and morphology depend on the natural conditions of the territory and also on anthropogenic activities. The soil properties (analyzed by conventional techniques) are moderate in acidity reaction and have relatively higher organic matter content. The Pb, Cu and Zn concentrations in anthropogenic horizons do not exceed the approximate permissible concentrations by 1.5–10-fold. Over the course of time, the soil profile has been transformed as a result of the impact of pedogenetic processes developing under the Mediterranean climate and man’s hand. Although urban environments present a certain complexity, at least the role of soil should be recognized regarding flood mitigation, recycling of wastes and toxins, filtering of nutrients or carbon storage and GHG regulation. The analysis of our results concludes the need to better perceive this soil profile and its green space to improve the urban ecosystem and to ensure better citizen well-being.